Strategy of Building Teamwork Toward an Adaptive Organization in The Vuca Era - Ismail, Dingot Hamonangan; Nugroho, Joko (Majalah Ilmiah Bijak, 2024)
This article discusses various strategies that can be used to build solid Teamwork as a prerequisite in creating a competitive and adaptive organization in the VUCA (Volatile) era of uncertainty (Uncertain), complex (Complex), and ambiguous (Ambiguous). In that era, an organization must be solid and collaborative to be agile, adaptable, and quick to make decisions. The researcher, with the approach of reviewing literature on several internationally accredited journals such as Scopus and Sinta as well as the study of the big theory of works by HR experts, found several strategies to build solid and collaborative Teamwork in the VUCA Era, namely: 1. Proper HR recruitment, 2. Introduction of the vision and mission and socialization of organizational culture from an early age to new employees; 3. Teamwork training must be systematically and measurably planned through conflict management training.